Oplan Hyglea a feasibility study for an oral health communication campaign for the urban poor of Metro Manila - Nobleza, Vince Marcus M.; Paragas, Jary Cedryck C.
The right to good health is fundamental and basic for everyone. The Philippines, being a developing country, is prone to serious threats in the general health and wellness of its citizens. Accordingly, Filipinos have always been at the forefront of vulnerability towards various diseases. One key health aspect Filipinos often forget and take for granted is their oral health. Oral health focuses on the well-being of the mouth, teeth, and gums. Poor oral health affects millions of Filipinos. Disease and other ailments, including those caused by poor oral health behavior, are often addressed through effective and efficient health policies. These interventions, however, can only be effectively carried out if information and knowledge about them are properly communicated. Correct and precise communication efforts are needed for public health interventions to be effective. Thus, this research is a feasibility study for an oral health communication campaign for the urban poor of Metro Manila. Results indicate that oral health is seen as a relevant health issue among the respondents. With high mean scores for perceived threat and perceived behavioral benefits, respondents therefore see the necessity of oral health as well as its relation to their overall health well-being. Results for both perceived severity and susceptibility support this findings as well. Respondents affirm oral health's impact in their daily lives and the consequences it may cause if not practiced properly. Furthermore, the acceptability of information about oral health and the use of seminars to impart such are high among the respondents. These findings signify the feasibility of an overall oral health communication campaign. This research thus proposes an integrated framework that can be used for perception and feasibility studies in the health sector. In line with this, it raises the importance and necessity of considering context as a relevant influencer towards health behavior change. Moreover, it assumes the finding that threat of a health issue is as relevant as its benefits. Thus, the two should be utilized in message design and implementation.